(untitled) (Research, Society and Development, 2020)
The present article originates from a research on technological competition teams from a Public University in the South of Minas Gerais aiming to analyze the relationships between CTS, active methodologies and training of engineers from that University. The methodological path included theoretical research on the historical context that shaped: the political and economic transformations of the 1970s and their educational and scientific and technological implications; The field research carried out qualitative interviews and made visits to the workshops. Individual interviews and a group with students - focus group - and individual interviews with teachers and coordinators of the competition teams were carried out. The form of treatment of the interviews was the content analysis of Bardin. The analysis of the interviews revealed that there is a positive response in the speeches of students and professors regarding a closer relationship between the university and the civil community, in order to generate artifacts and processes aimed at more vulnerable populations. The big question would be ‘how’ to bring these social demands to the academy. We conclude that students are interested in applying the theoretical knowledge they receive at the university in solving real problems, in working in a collaborative and interdisciplinary way, using creativity to build artifacts and to solve social issues and, in this sense, we reached our goal that was to analyze the relationships between Science And Technology And Society (CTS), active methodologies and training of engineers at a University South of Minas Gerais.